MEMBONGKAR POSITIVISME HUKUM DALAM KUHP PERSPEKTIF HUKUM ISLAM UPAYA MENEGAKKAN KEADILAN HAM KAUM PEREMPUAN DI INDONESIA - Habib Shulton Asnawi (Nizham Jurnal Studi Keislaman, 2013)
Law enforcement (judges, prosecutors and police) in Indonesia is still dominated by the positivistic paradigm and-legalistic way of thinking, especially in the legal meaning of the Criminal Code. The way to think of this kind proved to make the process of law enforcement in Indonesia is arid dry from morality. As a result, justice becomes the ultimate goal of law is often not achieved. Especially is justice and Human Rights (HAM) women. The inequality of women is certainly contrary to the concept of Indonesia as the "rule of law". As in Article 1 (3) UUD 1945 Indonesia is the "rule of law". The hallmark of the Rule of Law (Rechtsstaat / Rule of Law) is a rule of law that protects human rights (Human Rights). Law as supreme commander (commander) should not ignore the value of the legal basis of "justice" and "human rights protection". Legal positivism in the Criminal and Code is a sharp criticism of the various theories, especially the law of Islam. In Islamic law the concept of justice, equality and the protection of human rights is a philosophy or principles that should not be overlooked. Therefore, efforts to dismantle legal positivism in the Criminal Code is a necessity.